Experimental study on penetration of dental implants into the maxillary sinus in different depths - Weijian ZHONG; Binke CHEN; Xin LIANG; Guowu MA (University of São Paulo, 2013)
The exposing of dental implant into the maxillary sinus combined with membrane perforation might increase risks of implant failure and sinus complications. Objective: The purpose of this study was to investigate the effects of the dental implant penetration into the maxillary sinus cavity in different depths on osseointegration and sinus health in a dog model. Material and Methods: Sixteen titanium implants were placed in the bilateral maxillary molar areas of eight adult mongrel dogs, which were randomly divided into four groups according to the different penetrating extents of implants into the sinus cavities (group A: 0 mm; group B: 1 mm; group C: 2 mm; group D: 3 mm). The block biopsies were harvested five months after surgery and evaluated by radiographic observation and histological analysis. Results: No signs of inflammatory reactions were observed in any maxillary sinus of the eight dogs. The tips of the implants with penetrating depth of 1 mm and 2 mm were found to be fully covered with newly formed membrane and partially with new bone. The tips of the implants with penetrating depth over 3 mm were exposed in the sinus cavity and showed no membrane or bone coverage. No significant differences were found among groups regarding implant stability, bone-to-implant contact (BIC) and bone area in the implant threads (BA). Conclusions: Despite the protrusion extents, penetration of dental implant into the maxillary sinus with membrane perforation does not compromise the sinus health and the implant osseointegration in canine.